Integration of fly ash and ground granulated blast furnace slag into palm oil fuel ash based geopolymer concrete: a review - Ying Yi Tan; Hanizam Awang; Noor Haida Mohd Kaus (Sustainable Structures)
The construction industry significantly depends on concrete due to its mechanical attributes and economy efficiency. The increase demand for building materials, particularly concrete, has resulted in overproduction of ordinary portland cement (OPC) and consequent significant release of carbon dioxide (CO2) into the atmosphere. For addressing these issues, alternative innovative and sustainable materials, such as geopolymer concrete, which utilised waste materials as binding agents have been introduced, leading to a reduction in CO2 emissions. Palm oil fuel ash (POFA) contains abundant silicates and aluminates, making it well-suited for use as binder in geopolymer concrete. On the other hand, POFA geopolymer concrete with high volume exhibits reduced early strength development, decreased workability, and an extended setting time. Therefore, this review paper emphasizes the need of including fly ash (FA) and ground granulated blast furnace slag (GGBS) into POFA-based geopolymer concrete. A notable result of the review is that the inclusion of aluminium oxide and iron (III) oxide in FA improves the chloride binding capability, resulting to a dense microstructure with high strength. In addition, the presence of calcium oxide in FA and GGBS enhances the creation of C-S-H, N-A-S-H, and C-A-S-H gels, resulting in a decrease in porosity and an enhancement of the fresh and mechanical characteristics. Furthermore, the use of FA improves the insulation and thermal efficiency of the geopolymer concrete. Therefore, integration of FA and GGBS in POFA geopolymer may enhanced the mechanical and durability qualities. Further study is required to optimize the composition of POFA, FA and GGBS in the mix, and researching new, cost-effective alkaline activators obtained from waste products offers another avenue for boosting the efficiency of geopolymer synthesis.